2016
DOI: 10.1155/2016/9529630
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Prevents Cartilage and Bone Degradation in Experimental Models of Arthritis

Abstract: Background. Icariin (ICA) is an active compound extracted from Epimedium brevicornum Maxim. Previous reports have shown that icariin has a clinically significant therapeutic effect on rheumatoid arthritis. However, little is known about the mechanism by which icariin inhibits cartilage and bone degradation. Methods. New Zealand rabbits were immunized with antigen-induced arthritis (AIA) and treated with icariin. Joint tissues from rabbits were studied by histological analysis, transmission electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The data of Wei et al . indicated that icariin suppressed articular bone loss and prevented joint destruction in rheumatoid arthritis [43]. In this study, we confirmed that PLGA/icariin scaffolds had good biocompatibility during in vitro experiments.…”
Section: Discussionsupporting
confidence: 81%
“…The data of Wei et al . indicated that icariin suppressed articular bone loss and prevented joint destruction in rheumatoid arthritis [43]. In this study, we confirmed that PLGA/icariin scaffolds had good biocompatibility during in vitro experiments.…”
Section: Discussionsupporting
confidence: 81%
“…EGCG protected ΔΨ m level against oxidative stress and acted as a pro-survival agent in NP cells via activation of PI3K/Akt signaling pathway [95]. Icariin, isolated from herba epimedii or horny goat weed, is a bioactive and peroxylated flavonol glycoside compound, which has been studied for the treatment of degenerative diseases of articular cartilage [96]. Icariin's anti-oxidative and mitochondrial protective effects are attributed to the activation of PI3K/Akt and Nrf2 signaling pathways, resulting in ΔΨ m restoration, decrease of ROS production, and apoptosis in NP cells [96,97].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Icariin, isolated from herba epimedii or horny goat weed, is a bioactive and peroxylated flavonol glycoside compound, which has been studied for the treatment of degenerative diseases of articular cartilage [ 96 ]. Icariin’s anti-oxidative and mitochondrial protective effects are attributed to the activation of PI3K/Akt and Nrf2 signaling pathways, resulting in ∆Ψ m restoration, decrease of ROS production, and apoptosis in NP cells [ 96 , 97 ]. Furthermore, it was supposed a probable cross talk between Nrf2 and PI3K/Akt for attenuating the mitochondrial damage and preserving the cellular redox homeostasis [ 97 ].…”
Section: Small Molecules Targeting Mitochondrial Dysfunction In Ivd Degenerationmentioning
confidence: 99%
“…The treatment of osteoporosis is still a challenge [15]. Icariin is an herbal substance extracted from the plant Epimedium, which has antiosteoporotic and anti-osteoarthritic effects [3][4][5][6][7], and promotes bone healing [16]. Several studies have suggested that icariin not only increases the osteogenic differentiation of bone mesenchymal stem cells [17][18][19], but also inhibits osteoclast differentiation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Icariin is a natural substance extracted from the herb Epimedium. Icariin has anti-osteoporotic and antiosteoarthritic effects [3][4][5][6][7], through promoting osteoblastogenesis, and suppressing osteoclastogenesis [8]. However, the mechanisms underlying its antiosteoporotic action are not fully understood.…”
Section: Introductionmentioning
confidence: 99%